The bilingual usage dictionary - Gabrovšek, Dušan (ELOPE (Ljubljana), 2020)
The paper highlights the dictionary of English usage as a type of specialized language dictionary. Such dictionaries have been created in either the time-honored prescriptivist tradition or the more recent descriptivist one. Virtually all dictionaries of English usage are monolingual, i.e. all-English. While most dictionaries of English usage have been designed for native speakers of English, there are also a few notable works made particularly for non-native speakers of the language. The main part of the paper is devoted to the suggestion and formulation of guidelines for creating a bilingual, specifically English/Slovene encoding-oriented usage dictionary as a useful, reliable, varied, and user-friendly work of reference intended primarily for advanced-level Slovene speakers of English. The dictionary offers some features that are uncommon in today's dictionaries, especially the use of both languages in many entries, and some entries challenging the user to find the solution to the language problem listed for themselves. The final section presents 20 selected entries from the envisioned usage dictionary.
Keywords: angleška jezikovna raba; angleško/slovenski slovar jezikovne rabe; dictionary of usage; English usage; English/Slovene usage dictionary; enojezični v. dvojezični; monolingual vs. bilingual; slovar jezikovne rabe